Simulation of fluorescent concentrators - Bendig, M.; Hanika, J.; Dammertz, H.; Goldschmidt, J.C.; Peters, M.; Weber, M. (2008 Symposium on Interactive Ray Tracing, 2008)
Fluorescent concentrators (see Figure 1) are developed and investigated in solar energy research in order to improve the efficiency and applicability of solar cells. This is achieved by concentrating even diffuse light on cloudy days on small solar cells, using a fluorescent dye enclosed in low-cost acrylic glass. We developed a Monte Carlo simulation model for fluorescent concentrators that makes it possible to test and improve different setups and to gain further insight into the physical processes. As it is a complicated topic, fluorescent light has been investigated very rarely in computer graphics. Recent advances in fast ray tracing give the opportunity to simulate complex physical processes using simple models. Changes of the setup and physical properties can be simulated and evaluated quickly, providing the necessary foundation for automatic optimization.